Breast self-examination education as an effort to promote early detection of breast cancer among women in the Al-Wahab religious study group Air Paoh Village - Aisyah Aisyah; Nelly Rustiati; Meilina Estiani; Suparno Suparno (Science Center Group, 2026)
Background: Breast cancer remains a major public health concern among women, while delayed recognition of breast abnormalities continues to reduce opportunities for timely diagnosis and treatment. Breast self-examination provides a practical approach for increasing breast awareness and encouraging women to seek professional evaluation when they identify unusual changes. However, limited knowledge and inadequate practical skills frequently prevent women from performing breast self-examination correctly and regularly. Objective: This community service programme aimed to improve the knowledge and practical skills of women in performing breast self-examination as an early breast cancer detection effort in the Al-Wahab religious study group, Air Paoh Village. Methods: The programme applied an integrated participatory health education approach involving 20 women from the Al-Wahab religious study group. The intervention included health counselling, PowerPoint presentations, printed leaflets, an educational video, direct demonstration using a breast phantom, and guided redemonstration. The implementation team assessed participants’ knowledge through pre-test and post-test questionnaires and evaluated their practical skills through direct observation using a structured checklist. The team analysed the data descriptively by presenting frequencies and percentages for each knowledge category and level of practical competence. Results: Before the intervention, 10 participants (50%) had poor knowledge, 10 participants (50%) had moderate knowledge, and no participant had good knowledge. After the intervention, 17 participants (85%) achieved good knowledge, three participants (15%) achieved moderate knowledge, and no participant remained in the poor-knowledge category. The proportion of participants with good knowledge therefore increased from 0% to 85%. The practical assessment also showed that all 20 participants (100%) could independently and correctly perform the essential steps of breast self-examination after receiving demonstration and guided practice. Conclusion: Integrated education using audiovisual materials, breast-phantom demonstration, and guided redemonstration effectively improved participants’ knowledge and practical competence in breast self-examination. Regular community-based education should be maintained to strengthen breast awareness and support the early recognition of breast abnormalities.